PANDANGAN SYEIKH MUHAMMAD ZAINUDIN DALAM KITABNYA SIRAJU HUDA: SIMPULAN AHLI TAKWA ATAS FITNAH DAJJAL - Pratama, Apri Nanda; Pratama, Vitto; Widodo, Wedy (JURNAL DIALOKA: Jurnal Ilmiah Mahasiswa Dakwah dan Komunikasi Islam, 2023)
Abstract: This research examines the views of Sheikh Muhammad Zainuddin Assumbawi on the Dajjal in his book "Sirajul Huda ila Bayani 'Aqaidit Taqwa" which is translated into Malay with the title "Light of Guidance To Declare All Conclusions of All Devoted Experts on the Slander of the Dajjal the End of Time". This study uses a descriptive qualitative method to describe Sheikh Zainuddin's views and understanding of the Dajjal. This study discusses a brief profile of Sheikh Zainuddin Assumbawi, who is a scholar, writer, and expert on Sufism from Sumbawa. He has many influential students in the archipelago and has spread true religious understanding to people in the region. In this research, the definition of Dajjal according to the views of Sheikh Zainuddin Assumbawi is presented. Dajjal is described as a human figure who will appear at the end of time as a great slander for mankind. He describes the Antichrist as a figure who is very cunning, deceitful and has extraordinary magical powers. Dajjal will try to deceive people by claiming to be God or a false prophet. This study also discusses the actions of the Dajjal which are included in the signs of end-time slander. Dajjal is said to be able to heal the blind and revive the dead. He also mentioned that the Dajjal will provide false fertility and prosperity as an attempt to deceive people. In addition, this study describes the characteristics of the Dajjal according to the views of Sheikh Zainuddin Assumbawi. Dajjal is described as having writing between his eyes, a big body, curly hair, and one-eyed.In closing, this study concludes that Sheikh Zainuddin Assumbawi's view of the Dajjal refers to the book "Sirajul Huda ila Bayani 'Aqaidit Taqwa". Dajjal is seen as an end-time slander with magical powers and aims to deceive people. Muslims are encouraged to strengthen their faith, deepen their religious knowledge, and pray to be protected from the temptations and slander of the Dajjal. Keywords: Views of Sheikh Zainuddin Assumbawi, book, antichrist, a sign of the apocalypse, deepened religious knowledge Keywords: Dajjal, views, Sheikh Zainuddin Assumbawi, Sirajul Huda ila Bayani 'Aqaidit Taqwa, slander, the end of time. Abstrak: Penelitian ini mengkaji pandangan Syeikh Muhammad Zainuddin Assumbawi tentang Dajjal dalam kitabnya Sirajul Huda ila Bayani 'Aqaidit Taqwa yang diterjemahkan ke dalam bahasa Melayu dengan judul "Pelita Petunjuk Kepada Menyatakan Segala Simpulan Segala Ahli Takwa atas Fitnah Dajjal sang Akhir Zaman. Penelitian ini menggunakan metode kualitatif deskriptif untuk menggambarkan pandangan dan pemahaman Syeikh Zainuddin tentang Dajjal. Penelitian ini membahas profil singkat Syeikh Zainuddin Assumbawi, yang merupakan seorang ulama, penulis, dan ahli tasawuf yang berasal dari Sumbawa. Beliau memiliki banyak murid yang berpengaruh di Nusantara dan telah menyebarkan pemahaman agama yang benar kepada orang-orang di wilayah tersebut.Dalam penelitian ini, dikemukakan pengertian Dajjal menurut pandangan Syeikh Zainuddin Assumbawi. Dajjal dijelaskan sebagai sosok manusia yang akan muncul pada akhir zaman sebagai fitnah besar bagi umat manusia. Beliau menggambarkan Dajjal sebagai sosok yang sangat licik, penipu, dan memiliki kekuatan sihir yang luar biasa. Dajjal akan berusaha memperdaya manusia dengan mengaku sebagai Tuhan atau Nabi palsu. Penelitian ini juga membahas perbuatan-perbuatan Dajjal yang termasuk dalam tanda-tanda fitnah akhir zaman. Dajjal dikisahkan memiliki kemampuan menyembuhkan orang buta dan menghidupkan orang yang sudah mati. Beliau juga menyebutkan bahwa Dajjal akan memberikan kesuburan dan kemakmuran palsu sebagai upaya untuk menipu manusia.Selain itu, penelitian ini menggambarkan ciri-ciri Dajjal menurut pandangan Syeikh Zainuddin Assumbawi. Dajjal digambarkan memiliki tulisan di antara kedua matanya, berbadan besar, berambut keriting, dan bermata sebelah. Dalam penutup, penelitian ini menyimpulkan bahwa pandangan Syeikh Zainuddin Assumbawi tentang Dajjal mengacu pada kitab "Sirajul Huda ila Bayani 'Aqaidit Taqwa". Dajjal dipandang sebagai fitnah akhir zaman yang memiliki kekuatan sihir dan bertujuan untuk menipu manusia. Umat Muslim dianjurkan untuk memperkuat iman, memperdalam pengetahuan agama, dan berdoa agar terlindung dari godaan dan fitnah Dajjal.